Experience Your (Virtual) Ideal Relationship: Utilization Of Binaural Recording Technology In Japanese Audio Drama As Escapism - Putu Rania Pavita Budijaya (Universitas Medan Area, 2022)
This article aims to understand how Japanese audio dramas that utilize binaural recording technology become escapism for their fans. This study uses the reference of Jean Baudrillard's theory of simulacrum and hyperreality to approach the problem, with the basic assumption that the use of binaural recordings in CD dramas can increase the listener's sensation of hyperreality and therefore serve as their escape from reality. Data were collected through a literature review method on literature related to the topic as well as observations on the CD drama fan community on the internet to be analyzed qualitatively. It was found that hyperreality is displayed in the storyline, characters, and setting of the drama CD which resembles an ideal reality. Binaural recording technology in CD drama is able to provide an immersive experience for fans complete with fantasy elements that are certainly more interesting than their reality. The characters offered as co-stars also have varied appearances and personalities so fans can choose a partner according to the criteria they desire. In the end, the elements that make up this CD drama also cloud their perception of a true romantic relationship and trap them in a continuous simulation.